Gamebirds : a guide to North American species and their habits - Sprunt, Alexander, 1898-1973.; Zim, Herbert S. (Herbert Spencer), 1909-1994; Irving, James Gordon (New York : Golden Press, 1961)
Pictures 89 game birds, identifying their breeding and wintering ranges, scientific and local names, size, weight, flight speed, and nesting and feeding habits.
includes index.
Keywords: Game and game-birds -- North America; Game and game birds -- North America